Vegetation richness and rarity in habitats of European conservation value in Ireland. - Waldren, Stephen (My University, 2020)
Species richness is widely used as a measure of biodiversity in quantifying the conservation value of sites or habitats and in researching ecological functioning, but it gives equal weighting to different species irrespective of their rarity. We developed a Rarity Co-efficient and related indices utilising plant species distribution records to investigate the significance of this limitation and applied these to quantitative vegetation plot data from Irish habitats of European importance. The conservation value of habitats and ecosystems differed markedly depending upon whether it was measured by species richness, species rarity or both richness and rarity. Application of abundance-weighting had noteworthy effects on index values at the community level; dominance of non-native or very common species reduced values, while abundance of rare species increased values. Index values varied along successional gradients occurring in coastal dune systems and saltmarsh. Almost no significant concordance was found between the rankings of habitats based on richness or rarity index values derived from vascular plant data and those based on index values derived from bryophyte data, therefore these taxonomic groups are poor surrogates for each other. Habitats were divided into three categories based on similar patterns in these rankings: (a) habitats with specialist vascular plants, (b) species-rich vascular plant habitats and (c) important bryophyte habitats. Habitat assessment criteria should reflect these broad differences in conservation value. Integration of rarity indices into site conservation value assessments is recommended.
PUBLISHED
Keywords: Species richness, Species rarity, Annex I habitats, Vascular plants, Bryophytes Indices; Smart & Sustainable Planet; BIODIVERSITY; BIOGEOGRAPHY; Biodiversity and Conservation; Biodiversity distribution; CONSERVATION; Conservation Biology; Conservation and wildlife biology; ECOLOGY; Nature conservation policy and practice; Plant Biodiversity; Plant distribution; plant community ecology